Extraction, gelation and microstructure of Bambara groundnut vicilins. (December 2019) - Diedericks, Claudine F.; de Koning, Linda; Jideani, Victoria A.; Venema, Paul; van der Linden, Erik
Abstract: Nowadays there is a growing interest in exploiting new sources of plant proteins as functional ingredients in food products. In recent years, Bambara groundnut ( Vigna subterranea (L.) Verdc.) [BGN] has been explored as such a potential plant protein source, as a means of value-addition to this leguminous crop. To elucidate on the macroscopic functionality of BGN protein isolates, the focus of our study was on the extraction and characterisation of the vicilin protein fraction as the known major storage protein present in legume seeds. BGN vicilin had a high protein content (91%) and formed the largest component in relation to the other protein fractions. Together with molecular weight profiles obtained with gel electrophoresis and size-exclusion chromatography coupled with light scattering, the purity of vicilin and its presence as the predominant protein fraction in BGN black-eye seeds were confirmed. The isoelectric point (pH 5.3), solubility profile (highest solubility 86% at NaCl concentrations above 200 mM) and thermal denaturation temperature (92 °C) of BGN vicilin correspond to the range reported for other legume vicilins. Furthermore, the gelation behaviour of BGN vicilin gels was investigated using dynamic oscillatory measurements. These data were further analysed with scaling models, which revealed that fractal scaling was best suited for description of the BGN vicilin gel networks. The gel microstructures were visualised with confocal laser scanning and scanning electron microscopy. Graphical abstract: Image 1 Highlights: Pure vicilins extracted from Bambara groundnut. Vicilin forms the major storage protein in Bambara groundnut black-eye seeds. Bambara groundnut vicilin gel networks are weak-link fractal structures.